(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
Emotional appeals have been proven to play an important role in advertising. In addition, many researchers have identified the influence of cultural background in the emotion-shaping process. As a result, advertisers have combined cultural and emotional appeals in their advertisements, using cultural values as the factor to evoke emotions of the audiences. Previous researchers have studied this model in both individualistic and collectivist cultures. However, research on this model in advertising in Vietnam - a collectivist culture - needs to be more extensive. This paper examines relevant case studies to strengthen the stand that advertisements intentionally made embracing Vietnamese cultural values have an emotional influence on the audiences. Content analysis was applied as a methodology in our research to demonstrate certain cultural factors’ influence on the emotions of ad viewers. Moreover, we examine the impact of advertising lyrics and images on consumers’ emotional responses in the Vietnamese cultural context using particular case studies. The research’s scope would only show how the advertisers apply the cultural elements to audiences’ emotions; any reaction measuring method would not be mentioned in this paper. Results showed that culture has an impact on the emotional component of advertising. In particular, Vietnam, a collectivist nation, had some cultural aspects, including patriotism, personal interdependence, and great consideration of social norms. Those influenced how specific emotions are evoked through advertising in Vietnam. In conclusion, relying on collectivist culture can elicit diverse emotional characteristics in Vietnamese advertising. These studies show that the above methodology can be used in practice and has some influence on the creation of advertising with a broad target audience since it focuses on the various and common emotions that the collectivist society elicits.